Ambient Air Temperature Does Not Predict whether Small or Large Workers Forage in Bumble Bees (Bombus impatiens). (1st December 2009) - Couvillon, Margaret J.; Fitzpatrick, Ginny; Dornhaus, Anna
Abstract : Bumble bees are important pollinators of crops and other plants. However, many aspects of their basic biology remain relatively unexplored. For example, one important and unusual natural history feature in bumble bees is the massive size variation seen between workers of the same nest. This size polymorphism may be an adaptation for division of labor, colony economics, or be nonadaptive. It was also suggested that perhaps this variation allows for niche specialization in workers foraging at different temperatures: larger bees might be better suited to forage at cooler temperatures and smaller bees might be better suited to forage at warmer temperatures. This we tested here using a large, enclosed growth chamber, where we were able to regulate the ambient temperature. We found no significant effect of ambient or nest temperature on the average size of bees flying to and foraging from a suspended feeder. Instead, bees of all sizes successfully flew and foraged between16 ∘ C and36 ∘ C . Thus, large bees foraged even at very hot temperatures, which we thought might cause overheating. Size variation therefore could not be explained in terms of niche specialization for foragers at different temperatures.